Gendered language features based on perceptions of Malaysian millennials in facebook communication - Kirstie Tet-Mei, Fung; Su-Hie, Ting; Kee-Man, Chuah (Penerbit Universiti Kebangsaan Malaysia, 2023)
The study examined gendered language features based on perceptions of Malaysian millennials in Facebook communication. The data were collected from 60 millennials who were Facebook users living in Malaysia. In the study, the millennials were asked to read 14 comments by other Facebook users and asked to state whether they were written by female or male users and to justify their identification of gender. An analysis framework made based on past findings on gendered language features was used to code the 14 Facebook comments as female or male features. The analysis showed that the accuracy of gender identification was about 50%. Comments identified as written by males were those containing straightforward and short comments, harsh language, male discussion topics, and societal roles. Conversely, comments identified as written by females were those containing advice, expression of emotions, empathy, female discussion topics, and polite language. The findings suggest that some language features are losing a clear gender identification. The gender-neutral features emerge from female users who also use words with profanities and insults, and write in an autonomous or directive manner, and male users who engage in attenuation/experience sharing, and interpersonal orientation/supportiveness. The study indicates that despite the association of Facebook comment features with gender, gender identity lines are getting blurred among millennial Facebook users, making gender identification more difficult.